If it's not what You are looking for type in the equation solver your own equation and let us solve it.
608679=x*x
We move all terms to the left:
608679-(x*x)=0
We add all the numbers together, and all the variables
-(+x*x)+608679=0
We get rid of parentheses
-x*x+608679=0
Wy multiply elements
-1x^2+608679=0
a = -1; b = 0; c = +608679;
Δ = b2-4ac
Δ = 02-4·(-1)·608679
Δ = 2434716
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{2434716}=\sqrt{36*67631}=\sqrt{36}*\sqrt{67631}=6\sqrt{67631}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-6\sqrt{67631}}{2*-1}=\frac{0-6\sqrt{67631}}{-2} =-\frac{6\sqrt{67631}}{-2} =-\frac{3\sqrt{67631}}{-1} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+6\sqrt{67631}}{2*-1}=\frac{0+6\sqrt{67631}}{-2} =\frac{6\sqrt{67631}}{-2} =\frac{3\sqrt{67631}}{-1} $
| 2x+3^-1/2=0 | | 30-6m=-6m-30 | | −1.7u+3=−3.8 | | -3(f-83)=6 | | -93×15x=6x+141 | | 2^(2x+2)+9(2)^(x)=-2 | | (2x+3^-1/2=0 | | 2=1.08^x | | 24=j/7+27 | | 8k+5-10=-20 | | 7y-1=(2y+3)-2 | | 56x+112=-168 | | 608=x*x | | p/2+4=5 | | (1+x)(2x+3)^-1/2=0 | | 3=m/4-1 | | (x*2+2x-5)=(-2x-4x+7) | | 4(x-1)/6=2(x+7)/11 | | 3(x=4)-1=-7 | | 17+m=8(m-4) | | 2(x+5)=3x+6x+24 | | 2(-2x-12)+4=-2x-2x-20 | | 5x+18=6x+x | | t/2+2=3 | | -2×-3=y | | 2x(x-3)(2x+1)=0 | | 3(y-50)-36=16 | | 17+m=8(m-4 | | 11/2y-1=3 | | -40=-2a+8(4-2a | | 1/3(18-6x)=8-2 | | 8.5x=17 |